A new species of Eotetranychus from France (Acari, Prostigmata: Tetranychidae) - Auger, Philippe; Migeon, A.; Flechtmann, C. H.w. (Zootaxa, 2003)
A new species of Eotetranychus (Acari, Prostigmata: Tetranychidae), namely Eotetranychus cumtiliarium n. sp., is described and illustrated from specimens collected on Tilia platyphyllos (Tiliacae) in northern France. A key to French species of Eotetranychus is provided.